Reconstruction of Agrarian Reform Policy Based on Presidential Regulation No. 62 of 2023: A Juridical Study on State Responsibility in Guaranteeing Citizens’ Constitutional Rights to Land - Shinta Pangesti; Ayu Rosita Nugiantari; Bagus Permadi; Vanny Vanny (Transpublika Publisher, 2026)
Land inequality remains a persistent issue in Indonesia, often leading to agrarian conflicts and limiting access for marginalized groups. Presidential Regulation No. 62 of 2023 was introduced to strengthen agrarian reform and uphold citizens’ constitutional rights to land. This study aims to examines Presidential Regulation No. 62 of 2023 as a key policy aimed at addressing inequality in land ownership in Indonesia, with a focus on how this regulation facilitates agrarian reform and resolves agrarian conflicts. The objective of this research is to evaluate the effectiveness of the policy in distributing land to marginalized communities and ensuring citizens’ constitutional rights to land. The method employed is a normative juridical approach, using library research as the technique for collecting legal materials. Data were gathered from primary sources, such as the regulation itself, and secondary sources, including books, journals, and previous studies on agrarian reform. The findings indicate that although this policy has the potential to reduce land inequality, its implementation faces significant challenges due to bureaucratic obstacles, political influence, and resistance from large landowners. This study concludes that the success of implementation largely depends on government commitment, effective oversight, and community involvement to ensure equitable land distribution and the resolution of agrarian conflicts.